Correlation of serum thyroid stimulating hormone level to predict benign or malignant nature of thyroid swelling - Rana, Sabi; Bista, Meera; Shrestha, Akriti; Bhandari, Property; Devkota, Sagar; Pradhan, Sujan; Sharma, Saurav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Thyroid enlargement is a common clinical problem encountered in ENT practice, thyroid cancer, by contrast is less common. Several imaging modalities, FNAB and biomarkers are available but a simple clinical or biochemical diagnostic criterion is still lacking. Serum TSH is a well- established growth factor for thyroid nodules and thus can be used as a simple and reliable test to predict the risk of having a thyroid malignancy in a patient with thyroid swelling. Objectives were to correlate serum TSH level with benign or malignant nature of thyroid swelling and to evaluate the use of TSH level in predicting thyroid malignancy. Methods: This was a prospective observational study conducted over a period of one year at department of otorhinolaryngology and head and neck surgery of a tertiary care center in Nepal involving a total of 61 patients with thyroid swelling who underwent thyroid surgery. Pre-operative serum TSH level was measured and correlated with final HPE diagnosis. Results: The study included 61 patients of which 30 (49.2%) were malignant on histopathology report. The mean TSH level for benign cases was 1.97 mIU/l±0.99 and that for malignant cases was 3.85 mIU/l±1.20 (p=0.000), thus showing higher level of mean serum TSH in malignant group and also more in differentiated thyroid cancer. Conclusions: Patients with higher range of TSH levels were more likely to have thyroid malignancy as compared to lower range even within normal value. Hence, serum TSH level can be a reliable marker to predict malignancy in thyroid swelling.